The Effect of Wordwall-Based Word Card Media on Increasing Creativity and Cognitive Development in Kindergarten - Herwanto; Eges Triwahyuni; Kustiyowati (Postgraduate, University of Mataram, 2025)
The transition period to formal schooling begins at the kindergarten level. The word card media in this study uses Wordwall-based. The objectives of this research are: To determine the effect of Wordwall-based Word Card Media on the creativity of students at TK Kemala Bhayangkari 21, and to determine the effect of Wordwall-based Word Card Media on the cognitive development of children at TK Kemala Bhayangkari 21. In this study, a quantitative approach is applied. The method used is a quasi-experiment. The research results show data that the Asymp sig (2-tailed) value is 0.000 < 0.05. These results can be concluded that there is a difference in creativity before and after the implementation of Wordwall-based Word Card Media. Secondly, based on the output results in the regression test and its interpretation, a significance value of 0.000 < 0.05 will be obtained, which means that there is an influence of Wordwall-based Word Card Media on children's cognitive development. the questionnaire on the use of Wordwall-based card Media and the student creativity questionnaire. The basis for drawing conclusions is if the sig. linearity deviation value > 0.05.